A new species of Apolysis Loew, 1860 from China (Diptera: Bombyliidae, Usiinae, Apolysini) - Yao, Gang; Yang, Ding; Evenhuis, Neal L.; Gharali, Babak (Zootaxa, 2010)
The genus Apolysis Loew, 1860 is a moderately species-rich bee fly genus with 116 decribed species in the world; 14 species in the Palaearctic, and one species in the Oriental. A new species from China is described: Apolysis galba sp. nov. and Apolysis beijingensis (Yang & Yang), comb. nov., is redescribed. A key to the genera of the subfamily Usiinae in China is presented.